Alcohol consumption is associated with widespread changes in blood DNA methylation: Analysis of cross‐sectional and longitudinal data. (2nd December 2019) - Dugué, Pierre‐Antoine; Wilson, Rory; Lehne, Benjamin; Jayasekara, Harindra; Wang, Xiaochuan; Jung, Chol‐Hee; Joo, JiHoon E.; Makalic, Enes; Schmidt, Daniel F.; Baglietto, Laura; Severi, Gianluca; Gieger, Christian; et al.
Abstract: DNA methylation may be one of the mechanisms by which alcohol consumption is associated with the risk of disease. We conducted a large‐scale, cross‐sectional, genome‐wide DNA methylation association study of alcohol consumption and a longitudinal analysis of repeated measurements taken several years apart. Using the Illumina HumanMethylation450 BeadChip, DNA methylation was measured in blood samples from 5606 Melbourne Collaborative Cohort Study (MCCS) participants. For 1088 of them, these measures were repeated using blood samples collected a median of 11 years later. Associations between alcohol intake and blood DNA methylation were assessed using linear mixed‐effects regression models. Independent data from the London Life Sciences Prospective Population (LOLIPOP) (N = 4042) and Cooperative Health Research in the Augsburg Region (KORA) (N = 1662) cohorts were used to replicate associations discovered in the MCCS. Cross‐sectional analyses identified 1414 CpGs associated with alcohol intake at P < 10 −7, 1243 of which had not been reported previously. Of these novel associations, 1078 were replicated ( P < .05) using LOLIPOP and KORA data. Using the MCCS data, we also replicated 403 of 518 previously reported associations. Interaction analyses suggested that associations were stronger for women, non‐smokers, and participants genetically predisposed to consume less alcohol. Of the 1414 CpGs, 530 were differentially methylated ( P < .05) in former compared with current drinkers. Longitudinal associations between the change in alcohol intake and the change in methylation were observed for 513 of the 1414 cross‐sectional associations. Our study indicates that alcohol intake is associated with widespread changes in DNA methylation across the genome. Longitudinal analyses showed that the methylation status of alcohol‐associated CpGs may change with alcohol consumption changes in adulthood. Abstract : We conducted a large‐scale epigenome‐wide association study of alcohol consumption. Cross‐sectional analyses identified 1414 CpG sites at which blood DNA methylation was associated with alcohol drinking. The majority of these associations had not been reported previously and were replicated using data from independent samples. Methylation changes appeared more pronounced in women, non‐smokers, and participants genetically predisposed to consume less alcohol; comparison of current, former, and never drinkers and longitudinal analyses showed that these changes are at least partially reversible. We conducted a large‐scale epigenome‐wide association study of alcohol consumption.